Assessment of tsunami damage to buildings in resilient Byblos City and uncertainty considerations - ICASP14; Makhoul, Nisrine; Schmidt, Franziska; Lee, Jong; Navarro, Christopher (My University, 2023)
Byblos is a UNESCO World Heritage Site due to its resilience quality, as it is one of the oldest continuously inhabited cities in the world. It thrived for over 7000 years, mitigating shocks and stresses and still adapting and growing. Byblos is prone to seismic and tsunami risks. The latter can be generated by the Mount Lebanon Thrust fault about 18 km far in the Mediterranean Sea, facing the major Lebanese coastal cities. The 9 July 551 earthquake generated by this fault of 7.5 magnitude was followed by a tsunami which caused the coastal cities to lose their strategic, cultural, and commercial roles for centuries. This paper identifies the tsunami hazard and scenarios for Byblos, then studies and assesses the tsunami damage to Byblos buildings by means of likely tsunami scenarios. The article discusses the need to embed the uncertainties modeling in the hazard and damage analysis. Finally, results are presented, and recommendations are offered for future developments.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED